2002
DOI: 10.1097/00007632-200212010-00007
|View full text |Cite
|
Sign up to set email alerts
|

New In Vivo Animal Model to Create Intervertebral Disc Degeneration and to Investigate the Effects of Therapeutic Strategies to Stimulate Disc Regeneration

Abstract: The results of this study suggest that disc degeneration can be induced by axial dynamic loading in the rabbit intervertebral disc. The compressed rabbit intervertebral discs were large enough for the application of local transmitters through a percutaneous approach. We anticipate that this animal model could be used as a basic model to study intervertebral disc degeneration and to investigate new local therapeutic strategies for maintaining disc health or initiating tissue repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(160 citation statements)
references
References 20 publications
9
138
0
13
Order By: Relevance
“…All animals of Comparison between the control group N (number N1-N5), the compression group (C1-C5) and the distraction group (D1-D3) this group showed lower intradiscal pressure when compared with N. Additionally, load application resulted in lower disc height in lateral radiograph, which verified disc compression and approximated the degree of disc degeneration. As reported earlier, morphology showed degenerative changes after 28 days of axial compression [10]. We believe that the IVD pressure decrease in compressed discs is consistent with earlier findings and support the concept of moderate disc degeneration.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…All animals of Comparison between the control group N (number N1-N5), the compression group (C1-C5) and the distraction group (D1-D3) this group showed lower intradiscal pressure when compared with N. Additionally, load application resulted in lower disc height in lateral radiograph, which verified disc compression and approximated the degree of disc degeneration. As reported earlier, morphology showed degenerative changes after 28 days of axial compression [10]. We believe that the IVD pressure decrease in compressed discs is consistent with earlier findings and support the concept of moderate disc degeneration.…”
Section: Discussionsupporting
confidence: 93%
“…Disc degeneration in animal models is still a matter of debate [1,[8][9][10][11][12][13]. Most studies with mechanically induced disc degeneration demonstrated a correlation between compression force and disc degeneration [1, 9, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among many genetic and environmental factors that may contribute to the development of IVDD, disc cell death through apoptosis appears to be a major component (Ariga et al 2001(Ariga et al , 2003Court et al 2001;Gruber and Hanley 1998;Kohyama et al 2000;Kroeber et al 2002;Lotz and Chin 2000;Lotz et al 1998;Park et al 2001aPark et al ,b, 2005Park et al , 2006Rannou et al 2004;Walsh and Lotz 2004;Wang et al 2006a;Zhao et al 2006Zhao et al , 2007, but the signal transduction pathways involved in disc cell apoptosis have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%